PENGARUH EVENT MARKETING DAN STORE ATMOSPHERE TERHADAP REVISIT INTENTION PENGUNJUNG DI CIPUTRA WORLD SURABAYA - HONGDIYANTO, CHARLY; HOMAN, HOWEN (Jurnal Keuangan dan Bisnis, 2020)
This research is intended to discover the impact of event marketing and store atmosphere on visitor’s intention to revisit Ciputra World Surabaya, due to the significancy problem on its lack of repeat visits. Researchers feel it is important to use event marketing and store atmosphere as determining variables for revisit intention apart from being supported by previous research, the pre-survey results also strengthen the writer's understanding. This research used a quantitative approach with a simple random sampling method. The number of research samples are visitors of Ciputra World Surabaya with the quantity of 100. The method used in this study is multiple linear regression analysis. The method of collecting data uses a questionnaire which is measured by a Likert scale and processed using SPSS. The independent variable in this reserach is event marketing and store atmosphere. The dependent variable in this research is the visitor’s intention to revisit. The results of this research indicates that event marketing and store atmosphere variables have a significant impact on revisit intention.